PENGARUH PROFESIONALISME DAN PENGALAMAN AUDITOR TERHADAP TINGKAT MATERIALITAS PEMERINTAH KABUPATEN BANYUASIN - Ananda, Rudi (Jurnal Akuntansi dan Bisnis, 2023)
The purpose of this study was to empirically prove the simultaneous and partial influence of auditor professionalism and experience on the level of materiality in examining government financial statements at the Internal Auditor Inspectorate of Banyuasin Regency. The population in this study were Internal Auditors of the Banyuasin Regency Inspectorate, 2015 year of observation, totaling 73 Auditors using a sample using a census technique where the entire population was used as a research sample. The data analysis technique uses multiple linear regression with statistical testing of the F test, t test, and determination test. The results of this study prove that simultaneously, Auditor Professionalism and Auditor Experience have a significant effect on materiality. In conclusion, the aspects of professionalism and experience are simultaneously very important for an auditor to reveal materiality. The better the professionalism and experience, the easier it is for the auditor to reveal materiality. Partially, Auditor Professionalism and Auditor Experience have a significant effect on materiality. The better the professionalism, the easier it is for the auditor to reveal materiality. In conclusion, the experience aspect is also very important for an auditor in disclosing materiality. The better the experience, the easier and faster the auditor uncovers materiality.